Peningkatan Kapasitas Keluarga Dalam Pemenuhan Self Care Pasien Tuberkulosis di Kelurahan Balocci Baru - Latif, Aulia Insani; Tiala, Nur Hijrah; Masahuddin, La (Idea Pengabdian Masyarakat, 2023)
Tuberculosis is still one of the deadliest infectious diseases and has claimed millions of lives over the years. Several factors such as treatment adherence including length of treatment, drug side effects and access to health services are factors in increasing TB mortality rates. Some people who have family members with a history of tuberculosis do not understand how to care for and increase the independence of TB patients, plus the lack of internet access which makes people less exposed to health information, this is a partner problem so it is important to hold counseling on how to care for family members with TB, as well as assistance in increasing the self-care independence of TB patients. The service method is lecture/counseling, accompanied by simulations and questions and answers. This community service is held in January-February in Balocci Baru Village, Kec. Balocci to be exact in the courtyard area of the Balocci Baru village office. The results of the service are in accordance with the plan where participants are able to understand increasing the independence of self-care for TB patients and are enthusiastic during the counseling and mentoring process.